SADD AD-DZARIAH PRESPECTIVE OF EFFECTIVENESS TUBAN LOCAL GOVERNMENT REGULATION NO. 09 OF 2012 ON REGIONAL SPATIAL PLANING OF SETTLEMEN IN COASTAL BORDER - Rodhotun Nimah (Al-Balad: Journal of Constitutional Law, 2020)
This Research focuses on the sad ad-dzariah Prespective of coastal settlements and the effectiveness of the Tuban Local Government Regulation Number 09 of 2012 concerning spatial planing on settlements on the coastal border of Glondonggede village, Tambakboyo District, Tuban Regency. The research method used is a type of empirical legal research using a sociological juridical approach. Meanwhile, the data sources used are primary, secondary and tertiary data sources. Methods of data collection using interviews, documentation and direct observation. Analysis of the data used in this research using qualitative descriptive analysis, by reducing the data, presenting the data and then drawing a conclusion. In this research, two conclusions were obtained, First, The fact is that the local government regulation is not effective due to the lack of firm action by the authorities and the lack of public awareness of the law. Second, if viewed from the viewpoint of Sad Ad-Dzari'ah, the construction of settlements on the coastal border is not in accordance with the objectives of the Shari'a, because the construction of settlements along the coast is a cause of greater danger.